The future of industrial policies in the new millennium: Toward a knowledge-centered development agenda - Mario Cimoli; Giovanni Dosi; Joseph E. Stiglitz (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2008)
While it is futile to search for any 'magic policy recipe' automatically yielding industrialization, the contributions to the book, we argue, do indeed help in identifying some basic ingredients and principles that successful policy arrangements historically had and have in common. In this concluding chapter we spell out some of them. They include: (i) an 'emulation philosophy' vis-à-vis the most promising technological paradigms; (ii) various measures safeguarding the possibility of 'infant industry learning', involving also the purposeful 'distortion' of market signals as they come from the international arena; (iii) explicit policies of capability-building directed both at education and training but also at nurturing and shaping specific corporate actors; (iv) a 'political economy of rent-management' favourable to learning and industrialization, while curbing the exploitation of monopolist positions; (v) measures aimed to foster and exploit a weak Intellectual Property Rights regime, especially with respect to the companies of the developed world; (vi) strategies aimed at avoiding the 'natural resource course'; (vii) 'virtuous' complementarities between industrial policies and macroeconomic management. Further the chapter discusses the opportunities and constraints associated with the current regimes of trade and IPR governance and puts forward some basic building blocks of a proposed new pro-developmental consensus fostering knowledge accumulation and industrialization in catching-up countries.
Keywords: 330; Development; Industrial Policies; Knowledge Accumulation; Catching-up; New International Consensus